Image-based siRNA screen to identify kinases regulating Weibel-Palade body size control using electroporation - Ketteler, Robin (Sci Data, 2017)
High-content screening of kinase inhibitors is important in order to identify biogenesis and function mechanisms of subcellular organelles. Here, we present a human kinome siRNA high-content screen on primary human umbilical vein endothelial cells, that were transfected by electroporation. The data descriptor contains a confocal fluorescence, microscopic image dataset. We also describe an open source, automated image analysis workflow that can be reused to perform high-content analysis of other organelles. This dataset is suitable for analysis of morphological parameters that are linked to human umbilical vein endothelial cell (HUVEC) biology.